UPAYA INDONESIA DALAM MENINGKATKAN EKSPOR BIJI KAKAO KE CHINA DI DALAM KERANGKA ASEAN-CHINA FREE TRADE AGREEMENT (ACFTA) PERIODE 2011-2016 - Setiya Darmawan, - (2018)
This study discusses Indonesia's efforts to increase the export of cocoa beans to China within the framework of the ASEAN-China Free Trade Agreement for 2011- 2016 period. ASEAN - China Free Trade Area is a form of agreement between ASEAN countries and China to create free trade area by eliminating barriers or non-tariff trade barriers, increasing market access for services, investment rules and regulations, as well as enhancing aspects of economic cooperation to to encourage the economic relations of ACFTA parties in order to improve the welfare of ASEAN and China communities. The purpose of this study is to analyze the efforts of Indonesia to China to be able to increase the export value of cocoa beans in ACFTA trade agreement. The theory used in this research is the theory of International Economic Cooperation and Free Trade. The research method used is qualitative descriptive by using case study approach. This study was conducted through interviews with four informants related to this case. The research finds that the effort from Indonesia to increase the value of export to China has three efforts, namely the Indonesian government to make the exit and import duty for cocoa beans, the GERNAS program. There is an external effort that is a bilateral meeting or diplomacy between Indonesia and China which is held in China itself that menyendakan about marketing and trading of cocoa beans in the Chinese market and also the workshop